Cooperative structures of interaction in a public school EFL classroom in Bogotá - Parga Herrera, Fernando (Colombian Applied Linguistics Journal, 2011)
In deprived socio cultural contexts like those characterizing the suburbs of Bogotá, cooperative learning (CL) appears as an alternative to cope with student problems of interpersonal communication and conflict derived largely from gossiping, information distortion, and verbal aggressiveness that result in an inappropriate learning environment. As a result of implementing this action research study with 8th graders in a public school of Usme, in the southeast of Bogotá, students’ original negative influence over their peers turned into positive mediation, featured by peer monitoring, peer correction, and peer feedback. Such a change, which was evident in class audio and video recordings, as well as successful CL task development, occurred thanks to the joint establishment of rules for cooperative interaction with their corresponding roles, functions, times, and spaces immersed in the implemented CL structures of interaction. This way, students raised awareness of the crucial factors involved in effective oral communication and the importance of reporting information accurately for well-informed opinions and decisions. Students’ improvement in the oral communication processes contributed significantly to a better classroom social environment for learning.